A catalyst for converting normal and para hydrogen suitable for wide range of low temperature conditions and preparation method thereof

By using the fiber magnetic catalyst FeMnOx ordered doped with Fe atoms, the problems of low catalytic performance and poor stability of existing catalysts are solved, and efficient conversion of positive secondary hydrogen and long-lived catalysts are achieved, which significantly improves the conversion efficiency of the catalyst and stability.

CN115920919BActive Publication Date: 2024-12-27QINGDAO CHUANGQI XINNENG CATALYSIS TECH CO LTD

Patent Information

Application Number
CN202210832769.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-15
Publication Date
2024-12-27
Estimated Expiration
2042-07-15

AI Technical Summary

Technical Problem

The existing secondary hydrogen conversion catalysts have problems such as low catalytic performance, poor uniformity, poor stability, low reuse rate and short life.

Method used

The fiber magnetic catalyst FeMnOx, which is ordered doped with Fe atoms, is prepared by cation exchange reaction and high-temperature calcination treatment, and forms a regular arrangement of Fe atomic chains and porous structures to enhance the self-rotation of the catalyst. Capability and stability.

Benefits of technology

Under a wide range of low temperature conditions (23K~77K), the conversion efficiency of the normal secondary hydrogen is achieved by more than 95%, and the life of the catalyst is significantly extended to more than 1400 hours.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115920919B_ABST
    Figure CN115920919B_ABST
Patent Text Reader

Abstract

The present invention relates to a catalyst for ortho-parahydrogen conversion suitable for a wide range of low-temperature conditions and a preparation method thereof. The catalyst is a fiber magnetic catalyst FeMnOx doped with Fe atoms in an orderly manner; the base material of the catalyst is α-MnO2, the α-MnO2 belongs to the tetragonal system, the unit cell parameter is #imgabs0#, the crystal structure is composed of 2×2 octahedral chains with shared edges, the XRD characteristic diffraction peaks are 2θ=12.8°, 18.1°, 25.7°, 37.5°, 49.8°, 56.3°, and the specific surface area measured by the BET test method is 100-150m 2 / g, and transmission electron microscopy shows that its microstructure is a fibrous structure with a diameter of 2 to 5nm and a length of 100nm to 500nm; when the catalyst is used for the ortho-parahydrogen conversion reaction, the ortho-parahydrogen conversion efficiency is more than 95%, and the catalyst life is more than 1400h; the wide range of low temperature conditions is 23K-77K. The coordination of Fe atoms with lattice oxygen in α-MnO2 can effectively avoid the deactivation of the catalyst caused by the change of the valence state of the metal component, thereby enhancing the stability and life of the catalyst, and is suitable for industrial-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the fields of chemistry, chemical engineering and catalysts, and in particular to a para-hydrogen conversion catalyst for liquid hydrogen conversion and a preparation method thereof. Background Art

[0002] Hydrogen energy is an ideal clean energy source with the advantages of being renewable, having high energy density and high calorific value. The use and storage of hydrogen energy plays an important role in the development of hydrogen energy, transportation and economy. Hydrogen has multiple forms, including gaseous, liquid and solid. Liquid hydrogen has the advantages of being easy to store and having a large expansion ratio when gasified, and is an important way to store hydrogen energy. Liquid hydrogen is usually used as a propellant for launch vehicles, a low-temperature cooling source in the 20K temperature zone, and is also an efficient liquid fuel. It plays an important role in the defense industry, aerospace and other fields.

[0003] Hydrogen molecules can be divided into two quantum spin isomers, orthohydrogen (O-H2) and parahydrogen (P-H2), according to the direction of rotation of hydrogen atoms. The two hydrogen atoms in orthohydrogen spin in the same direction, while the two hydrogen atoms in parahydrogen spin in opposite directions. Normally, hydrogen is a mixture of orthohydrogen and parahydrogen. Gaseous hydrogen does not undergo ortho-parahydrogen conversion, while the equilibrium concentration of the mixture of orthohydrogen and parahydrogen in liquid hydrogen varies with temperature. At room temperature, the ratio of orthohydrogen to parahydrogen in the equilibrium state is 3:1, that is, 75% orthohydrogen and 25% parahydrogen; as the temperature decreases, orthohydrogen with a high energy ground state spontaneously converts to parahydrogen with a low energy state, and the concentration of parahydrogen continues to increase; at a temperature of 77K, the orthohydrogen content is 51% and the parahydrogen content is 49%; at 20.4K, the boiling point of liquid hydrogen, the parahydrogen content is as high as 99.8%.

[0004] However, the conversion time of ortho-parahydrogen itself is very long, and it will release a lot of heat and cause hydrogen loss. Under certain conditions, the conversion of ortho-hydrogen to para-hydrogen can be accelerated, which is referred to as the OP state conversion of hydrogen. The essence is the reorganization of the spin directions of the two atomic nuclei. At present, the methods for converting para-hydrogen and ortho-hydrogen include neutron impact method, laser irradiation method, catalyst method, etc.

[0005] The catalyst method is mainly based on the magnetic mechanism of the mutual conversion between orthohydrogen and parahydrogen. The essence of the magnetic theory is that there is an interaction between the magnetic center of the magnetic catalyst and the two spinning hydrogen nuclei with non-zero magnetic moments, which accelerates the spin transformation process of hydrogen molecules. The non-uniform magnetic field of the magnetic catalyst changes the spin orientation of the atomic nuclei in the hydrogen molecules. Assuming that in an extremely non-uniform magnetic field, the two atomic nuclei of hydrogen are distributed in different magnetic field strength environments, under the action of the magnetic field, the spin directions of the two atomic nuclei change, realizing the mutual conversion between orthohydrogen and parahydrogen.

[0006] Commonly used catalysts for the conversion of normal and para hydrogen include activated carbon, chromium-aluminum alloy, nickel-chromium alloy, Fe2O3·3H2O, Cr2O3, Apachi, Houdry, Fe(OH)3, Cr(OH)3, Mn(OH)4, nickel, chromium, manganese, etc.

[0007] CN112044457A discloses a supported normal-parahydrogen conversion catalyst and a preparation method thereof, and particularly relates to a preparation method of a supported normal-parahydrogen conversion catalyst by loading a metal active substance on the surface of a non-metal-modified porous carrier. The invention is simple in preparation of a supported catalyst, and the prepared supported catalyst has high strength and uniform particles, which effectively reduces the flow resistance of the catalyst bed, so that the catalyst activity is significantly improved compared to the traditional hydrated iron oxide catalyst. However, the inventive catalyst is prone to the problem of decreased stability due to changes in the valence state of the active metal component.

[0008] CN112844443A discloses a para-hydrogen conversion catalyst used in a liquid hydrogen production and storage device and a preparation method thereof. In particular, it relates to a supported para-hydrogen conversion catalyst prepared by using an ordered mesoporous material as a carrier, impregnating and roasting by a chemical precipitation method and then molding. Using an ordered mesoporous material as a carrier can effectively reduce the ineffective path for hydrogen molecules to enter the carrier, increase the adsorption rate of hydrogen molecules on the inner surface of the carrier, help reduce the flow resistance of the device, and improve the para-hydrogen conversion rate of the para-hydrogen catalytic conversion reaction at different space velocities. However, the method of impregnation before molding is prone to covering the catalytically active components, and the mass activity is lower than that of a granular catalyst.

[0009] CN113797928B discloses a para-hydrogen conversion catalyst for liquid hydrogen storage and a preparation method thereof, comprising: A) preparing an iron salt solution and a metal ion solution to be doped; B) preparing a doped iron salt solution: dripping the prepared metal ion solution to be doped into the iron salt solution in a certain proportion, and magnetically stirring at room temperature to obtain a doped iron salt solution; C) preparing a precursor: taking an appropriate amount of alkaline solution and dripping it into the doped iron salt solution obtained in step B) until the pH value of the mixed solution reaches 3 to 5; D) hydrothermal crystallization to obtain a finished product. The para-hydrogen conversion catalyst prepared by the invention can always maintain high activity in the entire temperature range of 20K to 80K, saving dosage. The catalyst is prepared by co-precipitation method, the particle size is large, and the problem of catalyst deactivation caused by changes in the valence state of the active component is prone to occur, and the defect of short catalyst life has not been solved.

[0010] Based on the above-mentioned prior art, the ortho-parahydrogen conversion catalyst prepared in the prior art has technical problems that need to be solved urgently, such as low catalytic performance, poor uniformity, poor stability, low reuse rate, and short life. Summary of the invention

[0011] In order to solve the technical problems existing in the above-mentioned catalyst and its preparation method, the present invention provides a highly efficient and stable catalyst for normal-parahydrogen conversion and its preparation method.

[0012] The invention provides a highly efficient catalyst for ortho-parahydrogen conversion under a wide range of low temperature conditions (23K-77K). The catalyst is a fiber magnetic catalyst (FeMnOx) doped with Fe atoms in an orderly manner and has high efficiency and high stability in catalytic conversion of ortho-parahydrogen.

[0013] The present invention provides a catalyst for converting liquid hydrogen into ortho-parahydrogen under a wide range of low temperature conditions. The catalyst is a fiber magnetic catalyst FeMnOx doped with Fe atoms in an orderly manner. The base material of the catalyst is α-MnO2, which belongs to the tetragonal system and has a unit cell parameter of The crystal structure is composed of 2×2 edge-sharing octahedral chains, and the XRD characteristic diffraction peaks are 2θ=12.8°, 18.1°, 25.7°, 37.5°, 49.8°, and 56.3°. The specific surface area measured by the BET test method is 100-150m 2 / g, and transmission electron microscopy (TEM) shows that its microstructure is a fibrous structure with a diameter of 2 to 5 nm and a length of 100 nm to 500 nm; when the catalyst is used for a para-hydrogen conversion reaction, the para-hydrogen conversion efficiency is more than 95%, and the catalyst life is more than 1400 hours; the wide range of low temperature conditions is 23K-77K.

[0014] The present invention also provides a method for preparing the above-mentioned catalyst, the method comprising:

[0015] 1) dissolving the iron salt precursor in water;

[0016] 2) mixing the substrate material α-MnO2 with the iron salt precursor solution in step 1) and stirring in a water bath, so that an ion exchange reaction occurs;

[0017] 3) After the ion exchange reaction is completed, the reaction solution of step 2) is filtered, washed, dried and calcined at high temperature, and the obtained powder is a catalyst for the conversion of normal and para hydrogen.

[0018] Furthermore, in the preparation method, the iron salt is any one of FeCl3, Fe(NO3)3, and Fe2(SO4)3.

[0019] Furthermore, in the preparation method, the concentration of Fe element in the iron salt precursor solution is 1 to 10 mol / L.

[0020] Furthermore, in the preparation method, the mass ratio of the base material α-MnO2 to the Fe element is α-MnO2:Fe=100:5-20, that is, the mass ratio of the base material to the converted Fe element.

[0021] Furthermore, in the preparation method, the temperature of the water bath is 60 to 90° C., and the reaction time is 6 to 24 hours.

[0022] Furthermore, in the preparation method, the drying temperature is 100 to 120° C., and the drying time is 8 to 24 hours.

[0023] Furthermore, in the preparation method, the high temperature calcination is carried out in an air atmosphere at a temperature of 600 to 900° C. and a calcination time of 1 to 6 hours.

[0024] Furthermore, in the preparation method, the powder has a mesh size of 40-80.

[0025] Furthermore, the preparation method of the base material α-MnO2 is as follows: dissolve 0.02 mol of MnSO4·5H2O(AR), 0.02 mol of (NH4)2S2O8(AR) and 0.06 mol of K2SO4(AR) in 70 ml of water, and mix and stir for 1 hour; transfer the uniformly mixed solution to a hydrothermal autoclave, and heat and crystallize at 140°C for 12 hours; after the reaction is completed, cool the solution to room temperature, wash the obtained dark brown powder with water 5 times, and dry it in an oven at 80°C for 12 hours to obtain magnetic nanofibrous α-MnO2.

[0026] The purpose of the high-temperature calcination treatment process is to reconstruct the skeleton of the disordered Fe elements on the surface of the catalyst after ion exchange under high temperature conditions, and transform it into a fiber magnetic catalyst doped with ordered Fe atoms.

[0027] The beneficial effects of the present invention are:

[0028] 1. The present invention uses nanofiber α-MnO2 as the base material, which has a large pore volume and pore diameter, with a pore volume of 0.5-0.8cm 3 / g, with an average pore size of 10 to 15 nm. The porous structure effectively improves the gas diffusion rate. Compared with commonly used silicon-based and aluminum-based carriers, since α-MnO2 contains manganese elements in various valence states, α-MnO2 has special magnetic properties and can be used as a catalyst for the conversion of normal and para-hydrogen.

[0029] 2. The present invention prepares the catalyst through cation exchange reaction and high-temperature calcination treatment, so the position of Fe atoms follows the periodic arrangement of Mn sites in the crystalline α-MnO2, thereby forming small, regularly arranged Fe atom chains, forming a non-uniform magnetic field between adjacent Mn atoms, and enhancing the catalyst's ability to induce hydrogen nucleus spinization.

[0030] 3. Fe atoms coordinate with lattice oxygen in α-MnO2 to form [FeO6] octahedron, which forms a hexagonal close-packed porous FeMnOx crystalline compound by sharing edges or corners with adjacent [MnO6] octahedrons. The pore size is 0.23-0.52nm. The crystal structure is composed of 2×2 edge-sharing octahedral chains. The chains are connected by oxygen atoms at the octahedral vertices, which can effectively avoid catalyst deactivation induced by changes in metal valence, thereby enhancing catalyst stability and life. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 XRD diagrams of the sample catalysts and the substrate material α-MnO2 obtained in Examples 1-3 of the present invention;

[0032] Figure 2 TEM images of the sample catalysts and the base material α-MnO2 obtained in Examples 1-3 of the present invention, wherein a-Example 1; b-Example 3; c-Example 3; d-α-MnO2;

[0033] Figure 3 This is the HAADF-STEM image of the sample catalyst prepared in Example 1 of the present invention; DETAILED DESCRIPTION

[0034] Example 1

[0035] A catalyst for normal-parahydrogen conversion of this embodiment comprises the following steps:

[0036] 1) Dissolve 48.6 g FeCl3 in 100 ml water;

[0037] 2) Mix 84 g of the substrate material α-MnO2 with the iron salt precursor solution in step 1), heat in a water bath at 80 degrees and stir for 12 hours, so that an ion exchange reaction occurs;

[0038] 3) After the ion exchange reaction is completed, the reaction solution of step 2) is filtered and washed 5 times, and the obtained black-brown powder is placed in an oven at 100°C for 12 hours, ground and calcined at 800°C in air for 6 hours at a heating rate of 3°C / min. The obtained powder is a catalyst for the conversion of normal and para-hydrogen, recorded as FeMnOx-1. Figure 1The XRD results show that the main diffraction peaks are 2θ=12.7°, 18.2°, 25.6°, 37.6°, 49.9°, and 56.2°. Figure 2 TEM showed that its microstructure was a nanofiber rod-like structure with an average diameter of 3nm and a length of 400nm.

[0039] Furthermore, the preparation steps of the substrate material α-MnO2 required for step 2) are as follows:

[0040] Dissolve 0.02 mol of MnSO4·5H2O(AR), 0.02 mol of (NH4)2S2O8(AR) and 0.06 mol of K2SO4(AR) in 70 ml of water, mix and stir for 1 hour; transfer the uniformly mixed solution to a hydrothermal autoclave, and heat and crystallize at 140°C for 12 hours; after the reaction, cool the solution to room temperature, wash the obtained dark brown powder with water 5 times, and dry it in an oven at 80°C for 12 hours to obtain magnetic nanofibrous α-MnO2. The preparation method of α-MnO2 required in Examples 2-3 is the same.

[0041] Example 2

[0042] A catalyst for normal-parahydrogen conversion of this embodiment comprises the following steps:

[0043] 1) Dissolve 124.05 g Fe(NO3)3 in 100 ml water;

[0044] 2) Mix 16.8 g of the substrate material α-MnO2 with the iron salt precursor solution in step 1), heat in a 90 degree water bath and stir for 6 hours, so that an ion exchange reaction occurs;

[0045] 3) After the ion exchange reaction is completed, the reaction solution of step 2) is filtered and washed 5 times, and the obtained black-brown powder is placed in a 120°C oven for drying for 8 hours, ground and calcined at 900°C in air for 3 hours at a heating rate of 3°C / min. The obtained powder is a catalyst for normal-parahydrogen conversion, recorded as FeMnOx-2. Figure 1 The XRD results show that the main diffraction peaks are 2θ=12.8°, 18.1°, 25.7°, 37.5°, 49.8°, and 56.3°. Figure 2 TEM showed that its microstructure was a nanofiber rod-like structure with an average diameter of 3nm and a length of 400nm.

[0046] Example 3

[0047] A catalyst for normal-parahydrogen conversion of this embodiment comprises the following steps:

[0048] 1) Dissolve 79.8 g Fe2(SO4)3 in 100 ml water;

[0049] 2) Mix 56.8 g of the substrate material α-MnO2 with the iron salt precursor solution in step 1), heat in a water bath at 80 degrees and stir for 12 hours, so that an ion exchange reaction occurs;

[0050] 3) After the ion exchange reaction is completed, the reaction solution of step 2) is filtered and washed 5 times, and the obtained black-brown powder is placed in an oven at 120°C for 12 hours, ground and calcined in air at 600°C for 12 hours at a heating rate of 3°C / min. The obtained powder is a catalyst for the conversion of normal and para-hydrogen, recorded as FeMnOx-3. Figure 1 The XRD results show that the main diffraction peaks are 2θ=12.7°, 18.3°, 25.6°, 37.6°, 49.9°, and 56.4°. Figure 2 TEM showed that its microstructure was a nanofiber rod-like structure with an average diameter of 3nm and a length of 400nm.

[0051] Comparative Example 1 Fe2O3 Catalyst

[0052] This comparative example is a catalyst for conventional normal-parahydrogen conversion, comprising the following steps:

[0053] 1) Preparing a precursor suspension using 0.3 M ferric nitrate, 0.3 M sodium hydroxide, and alcohol / water in a volume ratio of 1:4;

[0054] 2) The precursor suspension prepared in step 1) is transferred to a hydrothermal kettle, and the hydrothermal kettle is placed in an oven at 180° C. for crystallization for 8 h;

[0055] 3) After the crystallization reaction is completed, wait for the hydrothermal autoclave to cool to room temperature, transfer the product to a centrifuge tube for centrifugation at a speed of 5000 rpm, and take out the solid product after centrifugation and wash it three times with ethanol;

[0056] 4) The sample prepared in step 3) was dried under vacuum at 60° C. for 8 h to obtain a para-hydrogen conversion catalyst, denoted as Fe2O3.

[0057] Comparative Example 2Fe2O3 / MCM-41

[0058] The para-hydrogen conversion catalyst supported by the conventional molecular sieve carrier in this comparative example comprises the following steps:

[0059] 1) Preparing a precursor suspension using 0.3 M ferric nitrate, 0.3 M sodium hydroxide, and alcohol / water in a volume ratio of 1:2;

[0060] 2) MCM-41 and the precursor suspension prepared in step 1) were transferred into a hydrothermal kettle at a solid-liquid ratio of 1:10, and the hydrothermal kettle was placed in an oven at 180° C. for crystallization for 8 h;

[0061] 3) After the crystallization reaction is completed, wait for the hydrothermal autoclave to cool to room temperature, transfer the product to a centrifuge tube for centrifugation at a speed of 5000 rpm, and take out the solid product after centrifugation and wash it three times with ethanol;

[0062] 4) The sample prepared in step 3) was dried at 60° C. in vacuum for 8 h to obtain a para-hydrogen conversion molecular sieve catalyst, denoted as Fe2O 3 / MCM-41.

[0063] Comparative Example 3Fe2O3 / α-MnO2

[0064] The supported normal-parahydrogen conversion catalyst of this comparative example, wherein the substrate material has not been pretreated by the present invention, comprises the following steps:

[0065] The precursor suspension was prepared using 0.3 M ferric nitrate, 0.3 M sodium hydroxide, and alcohol / water in a volume ratio of 1:2;

[0066] 1) placing α-MnO2 and the precursor suspension prepared in step 1) into a hydrothermal kettle at a solid-liquid ratio of 1:10, and placing the hydrothermal kettle in an oven at 180° C. for crystallization for 8 h;

[0067] 2) After the crystallization reaction is completed, wait for the hydrothermal autoclave to cool to room temperature, transfer the product to a centrifuge tube for centrifugation at a speed of 5000 rpm, and take out the solid product after centrifugation and wash it three times with ethanol;

[0068] 3) The sample prepared in step 3) was dried under vacuum at 60° C. for 8 h to obtain a para-hydrogen conversion molecular sieve catalyst, which was recorded as Fe2O3 / α-MnO2.

[0069] The effects of the para-hydrogen conversion catalysts prepared in Examples 1-3 and Comparative Examples 1-3 of the present invention were tested by the following method:

[0070] ① The XRD analysis of the samples prepared in the present invention was performed using a Rigaku Ultima IV instrument for scanning and testing, and the MDIJade v6.0 software was used to analyze the peak height and peak area of ​​each element.

[0071] Figure 1 The XRD spectra of samples FeMnOx-1, 2, 3 and α-MnO2 prepared in Examples 1-3 match the standard spectra of fibrous α-MnO2 (JCPDS: 44-0141), and no peaks related to the Fe element are detected, indicating that the Fe element is highly dispersed. It can be seen that the α-MnO2 crystal structure has not changed significantly before and after loading.

[0072] ② The TEM morphology of the sample prepared in the present invention was observed using a JSM-6700F scanning electron microscope, and the sample morphology was measured using imageJ analysis software. The atomic structure of FeMnOx-1 was imaged using a high-angle annular dark field scanning transmission electron microscope (HAADF-STEM) after spherical aberration correction.

[0073] Figure 2 The microscopic morphology of samples FeMnOx-1, 2, 3 and α-MnO2 prepared in Examples 1-3 in the TEM spectra did not change significantly, proving that the ion exchange reaction and high-temperature calcination treatment did not change their basic fibrous morphology. The morphology was all nanofiber rods with a diameter of 2 to 5 nm and a length of 100 to 500 nm.

[0074] Figure 3 The sample FeMnOx-1 prepared in Example 1 has uniformly spaced bright spots as shown in the HAADF-STEM characterization results, which is the same as the periodic arrangement of Mn in the α-MnO2 (110) crystal plane. The atomic spacing is Corresponding Fe-Fe(d Fe-Fe ), which matches the theoretical Mn-Mn interatomic distance (2.9A), proving the formation of Fe atomic chains and atomic arrays, and also observing irregular FeOx nanoclusters with multiple atomic layers of thickness. This proves that the catalyst prepared by the present invention through cation exchange reaction and high-temperature calcination treatment, the position of Fe atoms follows the periodic arrangement of Mn sites in crystalline α-MnO2, forming small, regularly arranged Fe atomic chains.

[0075] ③Normal-parahydrogen conversion reaction: The main reaction is carried out in a low-temperature Dewar tank. The operation is divided into three temperature points, which are 77K, 65K and 23K. When operating under a temperature environment of 77K, liquid nitrogen is used as the refrigerant, and the pressure in the liquid nitrogen tank is controlled by the back pressure valve on the liquid nitrogen storage tank to ensure the stability of the refrigerant at a temperature of 77K. When operating under a temperature environment of 65K and 23K, helium is used as the refrigerant, and the tank pressure is controlled by a back pressure valve to ensure the stability of the refrigerant at temperatures of 65K and 23K. The catalyst mesh size is 20-30 meshes, the reaction space velocity is 1200mL·H2 / min / mL·catalyst, and the reaction pressure is 2.1MPa.

[0076] The gas outlet of the reactor containing the catalyst is connected to a gas chromatograph, and the content of parahydrogen is obtained by using the TCD detector of the gas chromatograph according to the difference in thermal conductivity between standard hydrogen and different hydrogen samples. The chromatographic column used is filled with 40-60 mesh 5A molecular sieve, the bridge current of the thermal conductivity cell is 200mA, the column temperature is room temperature, the carrier gas is standard hydrogen, and the carrier gas flow rate is 30ml / min.

[0077] As can be seen from Table 1, the samples FeMnOx-1, 2, and 3 prepared in Examples 1-3 have a conversion efficiency of ortho-parahydrogen of more than 95% in a wide range of low temperatures (77K, 65K, and 23K), and excellent stability, with a lifespan of more than 1400 hours; while the lifespan of the comparative examples is only 165 hours, 245 hours, and 367 hours. The reason is that the present invention prepares the catalyst by cation exchange reaction and high-temperature calcination treatment, so the position of the Fe atoms follows the periodic arrangement of the Mn sites in the crystal α-MnO2, thereby forming a small, regularly arranged Fe atom chain, forming a non-uniform magnetic field with adjacent Mn atoms, and enhancing the catalyst's ability to induce hydrogen nucleus self-spinning; Fe atoms coordinate with lattice oxygen in α-MnO2 to form iron oxide octahedrons, and form porous FeMnOx crystalline compounds of various configurations by sharing edges or corners with adjacent manganese oxide octahedrons, which can effectively avoid the catalyst deactivation induced by changes in metal valence, thereby enhancing the catalyst stability and lifespan.

[0078] Table 1 Examples 1-3, Comparative Examples 1-3, and the catalytic performance of substrate materials α-MnO2 and MCM-41 for normal and secondary hydrogen

[0079]

[0080]

[0081] Note: Catalyst life is calculated as the time required for the conversion efficiency to reach below 97% of the initial activity.

[0082] In Comparative Example 1, the sample is Fe2O3 catalyst, which is a traditional catalyst for para-hydrogen conversion. It can be seen that the initial activity of the catalyst is not much different from that of Comparative Examples 1-3, because iron oxide is an excellent para-hydrogen conversion catalyst. However, as the reaction proceeds, the reduced hydrogen can easily cause the valence state of iron oxide to change, from a high-valent state and strong magnetism to a low-valent state and weakly magnetic iron oxide catalyst, and the catalytic activity decreases rapidly.

[0083] In comparative example 2, the sample is Fe2O3 / MCM-41 catalyst, which is a conventional supported catalyst for ortho-parahydrogen conversion. It can be seen that the initial activity and lifespan are lower than those of samples FeMnOx-1, 2, and 3 prepared in Examples 1-3. This is because the present invention uses nanofiber α-MnO2 as the substrate material, which has a larger pore volume and pore size, with a pore volume of 0.5 to 0.8 cm 3 / g, with an average pore size of 10-15nm, and the porous structure effectively improves the gas diffusion rate; compared with the commonly used silicon-based and aluminum-based carriers, since α-MnO2 contains manganese elements in various valence states, α-MnO2 has special magnetic properties and has the ability to catalyze the conversion of normal and secondary hydrogen, and its catalytic activity is significantly better than that of the MCM-41 molecular sieve carrier. The catalyst is prepared by cation exchange reaction and high-temperature calcination treatment, with regularly arranged Fe atomic chains, forming a non-uniform magnetic field with adjacent Mn atoms, which enhances the catalyst's ability to induce hydrogen nuclear spin rotation.

[0084] In comparative example 3, the sample is Fe2O3 / α-MnO2 catalyst, which is a supported catalyst. It can be seen that although the initial activity is close to that of samples FeMnOx-1, 2, and 3, the life is much shorter than that of the samples prepared in Examples 1 to 3. This is because although the supported catalyst can support and disperse the active components, as the reaction proceeds, the reduced hydrogen easily causes the valence state of iron oxide to change from a high-valence state with strong magnetism to a low-valence state with weak magnetism, and the activity of the iron oxide catalyst decreases rapidly.

[0085] It should be understood that the present invention is not limited to the processes and structures described above and shown in the drawings, and various modifications and changes can be made without departing from the scope thereof. The scope of the present invention is limited only by the appended claims.

Claims

1. A catalyst for the conversion of normal and secondary hydrogen suitable for a wide range of low temperature conditions, characterized in that: The catalyst is a fiber magnetic catalyst FeMnOx doped with Fe atoms in an orderly manner; the base material of the catalyst is α-MnO2, which belongs to the tetragonal system, and the crystal structure is composed of 2×2 octahedral chains with shared edges, and the XRD characteristic diffraction peaks are 2θ=12.8°, 18.1°, 25.7°, 37.5°, 49.8°, and 56.3°. The pore volume of the base material α-MnO2 is 0.5-0.8cm 3 / g, the average pore size is 10-15nm, and the specific surface area measured by BET test method is 100-150m 2 / g, transmission electron microscopy shows that the microstructure is a fibrous structure with a diameter of 2-5nm and a length of 100nm-500nm; Fe atoms coordinate with lattice oxygen in α-MnO2 to form [FeO6] octahedrons, and form hexagonally densely packed porous FeMnOx crystalline compounds by sharing edges or corners with adjacent [MnO6] octahedrons; when the catalyst is used for normal-parahydrogen conversion reaction, the normal-parahydrogen conversion efficiency is more than 95%, and the catalyst life reaches more than 1400h; the wide range of low temperature conditions is 23K-77K; The preparation method of the catalyst comprises: 1) dissolving the iron salt precursor in water; 2) mixing the substrate material α-MnO2 with the iron salt precursor solution in step 1) and stirring in a water bath, so that an ion exchange reaction occurs; 3) After the ion exchange reaction is completed, the reaction solution of step 2) is filtered, washed, dried and calcined at high temperature, and the obtained powder is a catalyst for normal-parahydrogen conversion; Wherein, the mass ratio of the base material α-MnO2 to Fe element is α-MnO2:Fe=100:5-20; The temperature of the water bath is 60-90°C, and the reaction time is 6-24h; The drying temperature is 100-120°C and the drying time is 8-24h; The high temperature calcination is carried out in an air atmosphere at a temperature of 600 to 900° C. for a calcination time of 1 to 6 hours; The preparation method of the base material α-MnO2 is as follows: dissolve 0.02 mol of MnSO4·5H2O, 0.02 mol of (NH4)2S2O8 and 0.06 mol of K2SO4 in 70 ml of water, and mix and stir for 1 hour; transfer the uniformly mixed solution to a hydrothermal autoclave, and heat and crystallize at 140°C for 12 hours; after the reaction is completed, cool the solution to room temperature, wash the obtained dark brown powder with water 5 times, and dry it in an oven at 80°C for 12 hours to obtain magnetic nanofibrous α-MnO2.

2. A method for preparing the catalyst according to claim 1, characterized in that: The method comprises: 1) Dissolve the iron salt precursor in water; 2) mixing the substrate material α-MnO2 with the iron salt precursor solution in step 1) and stirring in a water bath, so that an ion exchange reaction occurs; 3) After the ion exchange reaction is completed, the reaction solution of step 2) is filtered, washed, dried and calcined at high temperature, and the obtained powder is a catalyst for normal-parahydrogen conversion; Wherein, the mass ratio of the base material α-MnO2 to the Fe element is α-MnO2:Fe=100:5-20; The temperature of the water bath is 60-90°C, and the reaction time is 6-24h; The drying temperature is 100-120°C and the drying time is 8-24h; The high temperature calcination is carried out in an air atmosphere at a temperature of 600 to 900° C. for a calcination time of 1 to 6 hours.

3. The method for preparing a catalyst according to claim 2, characterized in that: The iron salt is any one of FeCl3, Fe(NO3)3, and Fe2(SO4)3.

4. The method for preparing a catalyst according to claim 2, characterized in that: The Fe element concentration in the iron salt precursor solution is 1-10 mol / L.

5. The method for preparing a catalyst according to claim 2, characterized in that: The powder is 40-80 mesh.

Citation Information

Patent Citations

  • Supported ortho-parahydrogen conversion catalyst and preparation method thereof

    CN112044457A

  • Catalysts for Liquid Hydrogen Conversion and Their Preparation Methods

    CN113797928B

  • Ortho-parahydrogen conversion catalyst using ordered mesoporous material and preparation method of ortho-parahydrogen conversion catalyst

    CN112844443A

Cited By

  • Primary and secondary hydrogen conversion catalyst and method for preparing the same

    CN119386868B

  • Preparation method of ortho-parahydrogen conversion catalyst

    CN119425693A

  • A process for the preparation of a primary-to-secondary hydrogen conversion catalyst

    CN119425693B

  • A bar-shaped primary and secondary hydrogen conversion catalyst and a method for preparing the same

    CN119425694B

  • Orthoparahydrogen catalyst and preparation method thereof

    CN119771507A